In the Landmark NEVSUN Ruling, the Supreme Court Triggers Debate on the Duties and Powers of the Court Itself and its Ability to Extend the Reach of Public International Law to Impact Private Corporations - Mendes, Errol (Lex Electronica, 2024)
There has always been tensions between Canadian courts attempting to uphold the constitutional role of legislatures to determine what laws can impose civil liabilities on non-state actors within its sovereign borders while also not ignoring the importance of international legal norms as a country that promotes the international rule of law. This article discusses how those tensions reached its zenith with the recent historic majority ruling of the Supreme Court of Canada in Nevsun, by extending the reach of customary international law to allow for the imposition of civil liabilities on private entities such as transnational corporations within the domestic legal system. Reviewing first the traditional positivist position of the country’s highest court -- that only prohibitive or mandatory rules of customary international law should be incorporated into Canadian domestic law in the absence of contrary legislation -- the author then examines how the Nevsun case may have challenged the constitutional limits of judicial power to create new rights and duties, particularly regarding the adoption of civil liability norms against transnational corporations. Essentially, the article discusses the potential impact of the majority ruling (including Justice Rosalie Abella) internationally, subscribing to the idea that the application of international law norms at the national level can have a significant global impact, as was previously the case in the landmark Reference re Secession of Quebec ruling.